Performance comparative of modified jatropha based nanofluids in orthogonal cutting process - Nor Athira, Jamaluddin; Norfazillah, Talib; Amiril, S. A.S. (Novel Carbon Resource Sciences, 2021)
As machining operation is getting crucial, thus nanotechnology has been considered in providing more effective performance to reduce friction coefficient and wear protection of both workpiece and tool. This study investigated effect of an inclusion of solid nanoparticle additives such hexagonal boron nitride (hBN), graphene, copper oxide (CuO) at 0.05 wt.% concentration in modified jatropha (MJO) based oil. The performance of nanofluids was evaluated by conducting friction and wear test via four-ball test as well as machining process through orthogonal cutting process. The attained results were then compared with synthetic ester. This present study revealed the MJO nanofluids (MJO + 0.05 wt.% hBN, MJO + 0.05 wt.% graphene and MJO + 0.05 wt.% CuO) showed higher lubrication performance as compared to the commercial synthetic ester in term of physical properties and tribological behaviour. This condition resulted in the excellent machining performance which was explained by the reduction in maximum cutting temperature, chip thickness, effect of morphology chip and tool-chip contact length. Therefore, the MJO nanofluids can be considered as a potential sustainable metalworking fluid to replace the usage of the currently used synthetic ester in machining operation.